2022
DOI: 10.3389/fimmu.2022.974872
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated hepatic lipid metabolism and gut microbiota associated with early-stage NAFLD in ASPP2-deficiency mice

Abstract: BackgroundGrowing evidence indicates that lipid metabolism disorders and gut microbiota dysbiosis were related to the progression of non-alcoholic fatty liver disease (NAFLD). Apoptosis-stimulating p53 protein 2 (ASPP2) has been reported to protect against hepatocyte injury by regulating the lipid metabolism, but the mechanisms remain largely unknown. In this study, we investigate the effect of ASPP2 deficiency on NAFLD, lipid metabolism and gut microbiota using ASPP2 globally heterozygous knockout (ASPP2+/-) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…34,35 However, the dysregulation of lipid metabolism often associated with health problems, for example, the disordered lipid metabolism, is an adverse factor for the development of CVD and NAFLD. [36][37][38] Our current research suggested that a low dosage of R-TFA improved the disordered lipid metabolism in the C57BL/6J mice fed a high-fat diet, and lipidomics analysis revealed that it rehabilitated the hepatic levels of 2 TGs, 3 PEs, 1 PC, 1 FA and 1 Cer, exhibiting a salutary effect. The arachidonic acid metabolic pathway links lipid metabolism with inflammation and plays a crucial role in the occurrence and progression of metabolism-related diseases (e.g., obesity, NAFLD and CVD).…”
Section: Papermentioning
confidence: 80%
“…34,35 However, the dysregulation of lipid metabolism often associated with health problems, for example, the disordered lipid metabolism, is an adverse factor for the development of CVD and NAFLD. [36][37][38] Our current research suggested that a low dosage of R-TFA improved the disordered lipid metabolism in the C57BL/6J mice fed a high-fat diet, and lipidomics analysis revealed that it rehabilitated the hepatic levels of 2 TGs, 3 PEs, 1 PC, 1 FA and 1 Cer, exhibiting a salutary effect. The arachidonic acid metabolic pathway links lipid metabolism with inflammation and plays a crucial role in the occurrence and progression of metabolism-related diseases (e.g., obesity, NAFLD and CVD).…”
Section: Papermentioning
confidence: 80%
“…Gut microbes (GM) play a pivotal role in metabolic homeostasis, and disruptions in gut microbial homeostasis can lead to the development of a variety of metabolic disorders, including MASLD [ 107 , 108 ]. Dysbiosis of the intestinal flora may increase the permeability of the intestinal barrier, which leads to enhanced absorption of fatty acids [ 109 ]. On the other hand, intestinal damage may induce liver damage by exposing the liver to bacteria and their products, such as endotoxins [ 110 ].…”
Section: Gut Microbial Dysbiosis In Masldmentioning
confidence: 99%
“…Altered gut microbial composition could increase pro-inflammatory factors like TNF-α and IL-6 by activating TLR4 signaling pathways [ 40 ]. In animal models, alterations in gut microbiota composition and barrier function by apoptosis-stimulating p53 protein 2 (ASPP2) global heterozygous gene knockout, along with upregulation of TLR4, have been observed in the progression of NAFLD [ 41 ]. Similarly, HFD can significantly increase the expression of TNF-α, TLR-2, TLR-4, IL-6, and NF-κB in the liver and ileum by altering the composition of the gut microbiota and the relative abundance of some intestinal flora to promote steatosis [ 42 ].…”
Section: Mechanisms Of Tlr4 Signaling Pathways In Mafldmentioning
confidence: 99%